Potensi Konflik Sosial Masyarakat Nagari Padang Sibusuk dengan Desa Kampung Baru Pasca Resolusi Konflik - Arisman Trisno; Junaidi Indrawadi; Susi Fitria Dewi; Maria Montessori (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This study aims to determine the potential conflict between Padang Sibusuk and Kampung Baru after conflict resolution. The research was conducted in the village of Padang Sibusuk and Kampung Baru, Sijunjung Regency. This study uses a qualitative approach to reveal how the existence of potential conflicts between the two regions today. Data was obtained through observation, interviews, FGD (Focus Group Discusion) and documentation studies. Data were analyzed using data analysis techniques proposed by Miles and Huberman which consisted of three processes, namely data reduction, data presentation and conclusion. The validity of the data was tested by triangulation of sources. The results of the study showed: The potential for conflict is still stored in the nagari community of Padang Sibusuk and Kampung Baru villages after conflict resolution.  Community leaders to the two parties in conflict have not shown their sincerity together to obey the revolution.   The resolution is only an agreement but to comply with it is far from the expectations of those in conflict.